Differentiation of Multiple Myeloma and Lytic Bone Metastases: Histogram Analysis. Issue 6 (November 2020) - Yildirim, Mustafa; Baykara, Murat
Abstract : Objective: Metastasis and multiple myeloma are common malignant bone marrow lesions. It may be difficult to distinguish because of similar imaging findings. The purpose of this study was to determine the value of histogram analysis on the computed tomography imaging. Methods: Twenty-three patients with primary tumor and 23 patients with multiple myeloma were included in the study. All patients had lytic bone lesions on the thorax and abdominal computed tomography scan with contrast. Multiple bone lesions of patients with primary tumor were accepted as metastasis. Multiple bone lesions of patients with multiple myeloma were accepted as multiple myeloma involvement. Histogram analysis was performed from lytic bone metastases and bone involvement of multiple myeloma. Results of both groups were compared. Results: In histogram analysis, minimum, median, and maximum gray level parameters were found to be significantly higher in lytic bone metastases ( P < 0.001). Conclusion: Computed tomography histogram analysis can be considered as a method to be used in the differentiation of multiple myeloma and lytic bone metastases.